2, 3‐Butanediol catabolism in Pseudomonas aeruginosa PAO1. (24th September 2018) - Liu, Qiuyuan; Liu, Yidong; Kang, Zhaoqi; Xiao, Dan; Gao, Chao; Xu, Ping; Ma, Cuiqing
Summary: 2, 3‐Butanediol (2, 3‐BD) is a primary microbial metabolite that enhances the virulence of Pseudomonas aeruginosa and alters the lung microbiome. 2, 3‐BD exists in three stereoisomeric forms: (2 R, 3 R )‐2, 3‐BD, meso ‐2, 3‐BD and (2 S, 3 S )‐2, 3‐BD. In this study, we investigated whether and how P. aeruginosa PAO1 utilizes these 2, 3‐BD stereoisomers and showed that all three stereoisomers were transformed into acetoin by (2 R, 3 R )‐2, 3‐butanediol dehydrogenase (BDH) or (2 S, 3 S )‐2, 3‐BDH. Acetoin was cleaved to form acetyl‐CoA and acetaldehyde by acetoin dehydrogenase enzyme system (AoDH ES). Genes encoding (2 R, 3 R )‐2, 3‐BDH, (2 S, 3 S )‐2, 3‐BDH and the E1 and E2 components of AoDH ES were identified as part of a new 2, 3‐BD utilization operon. In addition, the regulatory protein AcoR promoted the expression of this operon using acetaldehyde, a cleavage product of acetoin, as its direct effector. The results of this study elucidate the integrated catabolic role of 2, 3‐BD and may provide new insights in P. aeruginosa‐ related infections.